Late payment mitigation mechanisms enacted by small construction businesses in the City of Johannesburg - Radebe, Malewa (University of the Witwatersrand, Johannesburg, 2021)
A late payment is one of the challenges that threaten the lifespan and existence of most of the Small Micro-Medium Enterprises (SMMEs). This study investigated the mechanisms which are devised by the construction SMMEs based in the Inner City of Johannesburg and doing business with the City of Johannesburg Municipality. A purposive sampling technique was utilized in selecting a sample of 20 SMMEs managers and owners from the target population. The semi-formal interviews were telephonically conducted to collect data. The study made significant findings as the collected data was analyzed. All the interviewed SMMEs indicated that they have and continue to face late payments when doing sub-contracting to the main contractors who get tenders from the clients (City of Johannesburg entities). To remain in business, the SMMEs implement various mechanisms which include making loans from the banks, friends, and loan sharks, making use of personal funds, credit facilities by the suppliers, and instructing lawyers to chase payments on behalf of the SMMEs. Most of the identified mechanisms are not sustainable, hence the research probed the SMMEs about their suggestions on resolving the late payment issue. Based on these recommendations, the study further made recommendations that will ensure that the challenge is dealt with, furthermore, how the effective mechanisms can be applied across the industry so that the construction SMMEs can run stable businesses that will grow and develop.
A research report submitted for the degree of Master of Management in Governance and Management at Wits School of Governance, the University of the Witwatersrand, Johannesburg, in 2024.
Keywords: Small Micro-Medium Enterprises (SMMEs); Inner City of Johannesburg; City of Johannesburg Municipality; South Africa; Construction Industry Development Board; UCTD; SDG-8: Decent work and economic growth